Antioxidant properties of flavonoids (Medical Journal of Indonesia, 2014)
Flavonoids represent a remarkable group of plant secondary metabolites and have long been used as traditional medicines with scientifically proven pharmacological benefits. They serve vast-ranging medicinal activities that may lead drug discovery with novel and potential therapeutic evidence. Latest research magnifies primarily functional activity of flavonoids as antioxidant against oxidative stress. This review enlightens the prospective role of flavonoids as antioxidant.